Microwave Plasma Torch Mass Spectrometry for Rapid Differentiation of Natural and Artificial Construction Stones - ZHOU Wei; XIONG Hai-long; YANG Mei-ling; CHEN Huan-wen; QU Ying; ZHANG Xing-lei; FANG Xiao-wei (Yankuang ceshi, 2014)
The distinction between natural stones such as marble and granite, and artificial stones formed mostly by unsaturated polyester resin with the addition of disintegrating slag of natural stone and some additives is difficult to determine accurately and quickly by chemical composition. Consequently, the development of Infrared Reflection Spectroscopy (IRS) has been established for for this purpose, but has limitations due to the high purity requirement of samples. Based on the high ability of thermal desorption and ionization of Microwave Plasma Torch (MPT), analyte could be ionized in a short time. In this study, Microwave Plasma Torch Mass Spectrometry (MPT-MS) was used to directly analyze natural and artificial stone without sample pretreatment. The fingerprint mass spectra of these stones were obtained in the mass range of m/z 50-1000. All data from artificial stones and natural stones were analyzed by principal component analysis (PCA) for differentiation of artificial and natural stones. The results show that abundant fingerprints of stones were acquired by MPT-MS. With the application of PCA, natural stones were successfully and rapidly differentiated from artificial stones. CO2 and H2O molecular clusters were desorbed from natural stones, however, organics (i.e. adhesives) were desorbed from artificial stone. Herein, MPT-MS is a new mass spectrometry technology under atmospheric pressure. Without the assistance of spray, laser, matrix and heat, the stones can be analyzed by MPT-MS directly. The method has high analytical speed (1 min per sample), high sensitivity, and does not require sample pretreatment. The results indicate that direct MPT-MS analysis allows rapid differentiation of untreated solid materials, such as construction stones, at the molecular level.